2004
DOI: 10.1177/0739456x04264919
|View full text |Cite
|
Sign up to set email alerts
|

Mobility Strategies and Food Shopping for Low-Income Families

Abstract: This article focuses on the relationship between the mobility constraints that low-income families face in their acquisition of food and the coping strategies they develop for this routine task. The motivations and rationale behind travel and provisioning choices of the working poor and the resources available to them are examined by means of a series of semistructured interviews conducted with members of twenty-six low-income house-holds residing in the Austin, Texas, area. The ways that these households cope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
151
0
7

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(164 citation statements)
references
References 13 publications
6
151
0
7
Order By: Relevance
“…Sloane and colleagues documented poorer availability of fresh fruits and vegetables, whole-grain foods, and low-fat dairy products in large chain supermarkets in African-American communities of Los Angeles than in more affluent, non-African-American areas 5 . In addition, as in other studies 28 , we found that most residents, including those in areas with lower availability of and access to supermarkets, report shopping in supermarkets. Nonetheless, persons with a chronic condition who reside in less advantaged areas may be more reliant on small markets and convenience stores for basic services in the intervals between trips to a supermarket.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Sloane and colleagues documented poorer availability of fresh fruits and vegetables, whole-grain foods, and low-fat dairy products in large chain supermarkets in African-American communities of Los Angeles than in more affluent, non-African-American areas 5 . In addition, as in other studies 28 , we found that most residents, including those in areas with lower availability of and access to supermarkets, report shopping in supermarkets. Nonetheless, persons with a chronic condition who reside in less advantaged areas may be more reliant on small markets and convenience stores for basic services in the intervals between trips to a supermarket.…”
Section: Discussionsupporting
confidence: 65%
“…FANS), we examined associations between the neighborhood food resource environment and health status for adults with, and those without, a chronic condition. Lower availability of healthy foods and easier access to less nutritious foods in disadvantaged areas may contribute to poorer health status through several mechanisms, including higher body mass index (BMI), stress associated with having to travel further and plan more carefully to obtain healthy foods, and time lost from other self-care activities [28][29][30] . We hypothesized that residence in an area with easier access to supermarkets would promote access to healthy foods, resulting in both lower rates of obesity and better self-rated health.…”
mentioning
confidence: 99%
“…Poor rural households also have less access to supermarkets and grocery stores (Kaufman 1999). As a consequence, residents in these areas face higher risk of obesity, diabetes and other diet-related illnesses (Gallagher 2006;Morland et al 2006;The Food Trust n.d.); food insecurity (Hendrickson et al 2006); are required to expend greater effort in grocery shopping (Clifton 2004); and receive less than optimal returns to government nutrition programs, such as food stamps and WIC (see Gallagher 2007).…”
Section: Explaining Disparities In Food Safety Compliancementioning
confidence: 99%
“…Vehicle data were included because automobile transport may influence perceived availability of healthy foods. 16,17 In addition, both vehicle and housing variables capture city and suburban differences in food availability. High income areas were included because they have been associated with greater availability of healthy foods.…”
mentioning
confidence: 99%